2016
DOI: 10.1155/2016/2152018
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigations and Analysis of Cu2ZnSnS4Based Solar Cells by SCAPS-1D

Abstract: This paper reports numerical investigation, using SCAPS-1D program, of the influence of Cu2ZnSnS4(the so-called CZTS) material features such as thickness, holes, and defects densities on the performances of ZnO:Al/i-ZnO/CdS/CZTS/Mo solar cells structure. We found that the electrical parameters are seriously affected, when the absorber thickness is lower than 600 nm, mainly due to recombination at CZTS/Molybdenum interface that causes the short-circuit current density loss of 3.6 mA/cm2. An additional source of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(25 citation statements)
references
References 16 publications
3
22
0
Order By: Relevance
“…It would be observed that the solar cells' performance does not change much when the defect density is below 10 14 cm −3 . This result tallies with the finding of similar study [24] in this regard. Figure 7 shows that all electrical performance parameters start degrading at a defect density of ≈ 10 15 cm −3 .…”
Section: Effect Of Multivalent Defect Concentration In Cigs (Absorber) Layersupporting
confidence: 93%
“…It would be observed that the solar cells' performance does not change much when the defect density is below 10 14 cm −3 . This result tallies with the finding of similar study [24] in this regard. Figure 7 shows that all electrical performance parameters start degrading at a defect density of ≈ 10 15 cm −3 .…”
Section: Effect Of Multivalent Defect Concentration In Cigs (Absorber) Layersupporting
confidence: 93%
“…6 A conversion efficiency of 15% was reported for the CZTS=CdS structure photovoltaic solar cell in 2016. 22 A conversion efficiency of 18:05% was presented for the CZTS=CdS structure solar cell in 2017. 23 Numerical analysis of the kesterite-based ZnO=CdS=CZTS=Mo solar cell is proposed in this work, and SCAP-1D is used for the simulation of a solar cell.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the different mechanisms of loss resulting from the nature of absorption. Therefore, the effects of thickness, doping, and defects must be analyzed to increase the efficiency of the cell [2]. New compounds can be studied by replacing Zn with certain elements (e.g.…”
Section: Introductionmentioning
confidence: 99%